If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2m(m + -1)(3m + -1) = 0 Reorder the terms: 2m(-1 + m)(3m + -1) = 0 Reorder the terms: 2m(-1 + m)(-1 + 3m) = 0 Multiply (-1 + m) * (-1 + 3m) 2m(-1(-1 + 3m) + m(-1 + 3m)) = 0 2m((-1 * -1 + 3m * -1) + m(-1 + 3m)) = 0 2m((1 + -3m) + m(-1 + 3m)) = 0 2m(1 + -3m + (-1 * m + 3m * m)) = 0 2m(1 + -3m + (-1m + 3m2)) = 0 Combine like terms: -3m + -1m = -4m 2m(1 + -4m + 3m2) = 0 (1 * 2m + -4m * 2m + 3m2 * 2m) = 0 (2m + -8m2 + 6m3) = 0 Solving 2m + -8m2 + 6m3 = 0 Solving for variable 'm'. Factor out the Greatest Common Factor (GCF), '2m'. 2m(1 + -4m + 3m2) = 0 Factor a trinomial. 2m((1 + -3m)(1 + -1m)) = 0 Ignore the factor 2.Subproblem 1
Set the factor 'm' equal to zero and attempt to solve: Simplifying m = 0 Solving m = 0 Move all terms containing m to the left, all other terms to the right. Simplifying m = 0Subproblem 2
Set the factor '(1 + -3m)' equal to zero and attempt to solve: Simplifying 1 + -3m = 0 Solving 1 + -3m = 0 Move all terms containing m to the left, all other terms to the right. Add '-1' to each side of the equation. 1 + -1 + -3m = 0 + -1 Combine like terms: 1 + -1 = 0 0 + -3m = 0 + -1 -3m = 0 + -1 Combine like terms: 0 + -1 = -1 -3m = -1 Divide each side by '-3'. m = 0.3333333333 Simplifying m = 0.3333333333Subproblem 3
Set the factor '(1 + -1m)' equal to zero and attempt to solve: Simplifying 1 + -1m = 0 Solving 1 + -1m = 0 Move all terms containing m to the left, all other terms to the right. Add '-1' to each side of the equation. 1 + -1 + -1m = 0 + -1 Combine like terms: 1 + -1 = 0 0 + -1m = 0 + -1 -1m = 0 + -1 Combine like terms: 0 + -1 = -1 -1m = -1 Divide each side by '-1'. m = 1 Simplifying m = 1Solution
m = {0, 0.3333333333, 1}
| -435+5x=141+23x | | 5-x=14-4x | | X=-m/b | | x+8-4x=25 | | X^3-6X+8=0 | | -72-24x=152-17x | | -2xy(3xy^3-5xy+7y^2)= | | -156-3x=4x+173 | | 5(x)6=126 | | -59+24x=139+21x | | 5(2m-3y)=25 | | 17x-348=4x+172 | | -16x+10x+100=0 | | 9x+2=x+18 | | 2x+8+7x=48 | | -305+19x=-x+315 | | 189-16x=4x+327 | | -3x-41=31-5x | | -64/9x+8 | | -17x-348=-4x+172 | | -20y+15=2-16y+11 | | Y=6x^2+7x-5 | | 3h^2+7h-880=0 | | -189-16x=-4x+327 | | (1+5i)+(-6+2i)=0 | | 1.2x+2=107.13 | | (5y+7)=32 | | 13x-61=33+11x | | y=1/4*4 | | a^2+10a+16= | | y=1/4*-8 | | 5(p+8)=136 |